Perbandingan Akurasi Pemeriksaan Imunohistokimia SOX10 dengan DOG1 dalam Mendiagnosis Karsinoma Sel Asinik Kelenjar Liur pada Sediaan FFPE - Ricky Handika; Ika Dhuhani; Nur Rahadiani (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2020)
BackgroundMorphological diversity is a challenge in establishing diagnosis of malignant tumor originated from salivary gland, especially Aciniccell carcinoma (ACC). Immunohistochemical (IHC) staining using DOG1 is often used to help diagnosis of ACC. Lately, IHC SOX10has been reported to have almost the same accuracy to DOG1 staining. This evidence-based case report aims to determine theaccuracy of SOX10 to DOG1 immunohistocheinstry staining in establishing a diagnosis of ACC.MethodsLiterature searches were carried out on the Pubmed, Clinical key, Proquest, ScienceDirect, Scopus, SpringerLink and Wileydatabases. Two journals were relevant to the clinical scenario, then a critical review is carried out using the Diagnostic StudyAppraisal Worksheet from the Center for Evidence-based Medicine, University of Oxford, 2010.ResultsThe accuracy of SOX10 in diagnosing ACC was slightly better than DOG1, with sensitivity reaching 100% and specificity reaching87.76%. The sensitivity of SOX10 and DOG1 is the same, but SOX10 is more specific, and positive predictive value is also betterthan DOG1.ConclusionThe accuracy of SOX10 is better than DOG1 in diagnosing ACC of salivary gland. However, the intensity of SOX10 staining tends tobe rather low compared to DOG1. Therefore, further research is still needed to recommend SOX10 staining in daily practice.